Spectral Doppler ultrasound in the major arteries of normal conscious immature micropigs - Jung, J.H., Seoul National University, Seoul, Republic of Korea; Chang, J.H., Seoul National University, Seoul, Republic of Korea; Oh, S.K., Seoul National University, Seoul, Republic of Korea; Choi, M.C., Seoul National University, Seoul, Republic of Korea (Journal of veterinary science (Suwŏn-si, Korea), 2010)
Spectral waveform analysis of blood flow velocity in the major arteries of six healthy, conscious immature micropigs was determined using Doppler ultrasonography. Doppler spectral tracings were recorded from the external iliac artery, femoral artery, and renal arcuate artery. Tracings were also taken from three parts of the common carotid artery and two parts of the abdominal aorta. Spectral Doppler parameters included peak systolic velocity, early diastolic velocity, peak systolic velocity-to-end diastolic velocity ratio, resistive index, and pulsatility index. In addition, the diameter of major arteries and indirect blood pressure were measured. These results from spectral Doppler analysis in major arteries may be useful as reference ranges in the future studies of vascular hemodynamics in immature micropigs.